Approximate controllability of delay nonautonomous integro‐differential system with impulses. (26th March 2022) - Kumar, Ankit; Vats, Ramesh K.; Dhawan, Kanika; Kumar, Avadhesh
Abstract : In this article, we consider the second‐order nonautonomous integro‐differential system with finite delay and noninstantaneous impulse. The aim of this paper is to establish the approximate controllability result for the proposed control problem. We use the evolution operator and Schauder's fixed‐point approach for proving our main result. Also, we provide an example to illustrate our main result.